2016
DOI: 10.1039/c6cc07079e
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and properties of a palladium PBP pincer complex featuring an ambiphilic boryl site

Abstract: The palladium diphosphinoboryl pincer [{(o-PPhCH)B}PdI] 8 was prepared from the diphosphinoborane complex 6a. The boryl functionality of the pincer displayed ambiphilic properties allowing: (1) coordination of Lewis basic pyridines to the boryl site and (2) access to palladium diphosphinoborane complex derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…1 H NMR (400 MHz, C 6 D 6 ): δ 8.20 (dd, 1H, 3 J HH = 6.9, 4.4 Hz, Ar p-H), 7.31 (t, 1H, 3 J HH = 7.2 Hz, Ar m-H), 7.17 (m, 1H, Ar o/m-H, signal partially obscured by solvent signal), 7.14 (m, 1H, Ar o/m-H, signal partially obscured by solvent signal), 3.22 (d, 1H, 2 J HH = 15.9 Hz, methylene CH 2 ), 2.95 (dd, 1H, 2 J HH = 15.1 Hz, 2 J HP = 12.3 Hz, methylene CH 2 ), 1.90 (m, 1H, ethylene CH 2 ), 1.48 (m, 1H, ethylene CH 2 ), 1.30 (m, 1H, ethylene CH 2 ), 1.17 (d, 9H, 3 J HP = 12.0 Hz, C(CH 3 ) 3 ), 1.14 (d, 9H, 3 J HP = 11.6 Hz, C(CH 3 ) 3 ), 1.11 (m, 1H, ethylene CH 2 ), 0.92 (dd, 3H, 3 J HP = 7.7, 4.5 Hz, NiCH 3 ), 0.76 (d, 9H, 3 J HP = 12.4 Hz, C(CH 3 ) 3 ). 31 (11). To a J Young NMR tube was added 10 (0.010 g, 0.023 mmol), PPh 3 (0.006 g, 0.02 mmol), and 1 mL of C 6 D 6 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (400 MHz, C 6 D 6 ): δ 8.20 (dd, 1H, 3 J HH = 6.9, 4.4 Hz, Ar p-H), 7.31 (t, 1H, 3 J HH = 7.2 Hz, Ar m-H), 7.17 (m, 1H, Ar o/m-H, signal partially obscured by solvent signal), 7.14 (m, 1H, Ar o/m-H, signal partially obscured by solvent signal), 3.22 (d, 1H, 2 J HH = 15.9 Hz, methylene CH 2 ), 2.95 (dd, 1H, 2 J HH = 15.1 Hz, 2 J HP = 12.3 Hz, methylene CH 2 ), 1.90 (m, 1H, ethylene CH 2 ), 1.48 (m, 1H, ethylene CH 2 ), 1.30 (m, 1H, ethylene CH 2 ), 1.17 (d, 9H, 3 J HP = 12.0 Hz, C(CH 3 ) 3 ), 1.14 (d, 9H, 3 J HP = 11.6 Hz, C(CH 3 ) 3 ), 1.11 (m, 1H, ethylene CH 2 ), 0.92 (dd, 3H, 3 J HP = 7.7, 4.5 Hz, NiCH 3 ), 0.76 (d, 9H, 3 J HP = 12.4 Hz, C(CH 3 ) 3 ). 31 (11). To a J Young NMR tube was added 10 (0.010 g, 0.023 mmol), PPh 3 (0.006 g, 0.02 mmol), and 1 mL of C 6 D 6 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Tridentate pincer-type ligands have been found useful for numerous applications in both catalytic and stoichiometric processes. While many different variations exist today, one of the original pincer ligands with flanking phosphine donors and a central anionic carbon donor (M­[PCP] in Chart ) continues to be explored. Related pincer ligands have replaced the central donor with other heteroatoms such as B, Si, and N, , and in each case, the effect of the different central donor is profound. Given our longstanding interest in PNP and PCP , donor sets, we were also interested in exploring different arrangements of donors around a central metal.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the carborane-derived boryls or the diaminoboryl in Chart , it may be expected that a diarylboryl would possess a higher degree of Lewis acidity. In a recent publication, we described syntheses of Ir and Rh complexes of this PBP ligand, while Tauchert et al reported on its Pd complexes . The synthetic introduction of the PBP ligand was accomplished via insertion of monovalent Ir or Rh into the B–Ph bond of 1 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 95–97 ] As pointed out in Scheme 11, pincer‐type complexes ( V ) with a central triarylborane moiety (Z‐type) can react via an intramolecular B–C‐oxidative addition to the boryl‐based (X‐type) pincer‐type complexes ( Va ). [ 42,63 ] In conclusion, it becomes evident that at least in pincer‐type complexes, all ligand types according to the CBC scheme Z‐, X‐ and L‐type, can undergo an intramolecular E–R‐oxidative addition giving rise to either X‐ or X 2 ‐type groups.…”
Section: Coordination Patterns With Non‐metal Ligating Atomsmentioning
confidence: 96%
“…The resulting palladium(II) iodido complex 9 was formed via concomitant C–C‐coupling. [ 63 ] The boryl group in complex 9 was demonstrated to be Lewis acidic via the coordination of pyridine. In this way the formation of a ligand‐stabilized boryl ligand R 2 LB – was achieved (R = anionic aryl substituents, L = neutral substituent such as pyridine).…”
Section: Coordination Patterns With Non‐metal Ligating Atomsmentioning
confidence: 99%